INTEGRATION OF ISLAM WITH LOCAL CULTURE: A STUDY OF MAUDHU LOMPOA TRADITION IN GOWA REGENCY - syukur, syamzan; Nuraeni, Nuraeni; Rahmat, Rahmat; Idris, Muh.; Kadril, Kadril (Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi, 2024)
This research is about the integration of Islamic culture with local culture in Maudhu Lompoa tradition in Gowa Regency. The aim of this research is to reconstruct the history of the integration of Islam with local culture. it described and analyzed the integration of Islam in the traditional processions, the integration of Islam into the values contained in tradition and the impact of the integration of Islam on people's lives. The results of this research will fill the gaps in previous academic studies and will be useful for the government in formulating policies regarding the management and preservation of traditions as well as empowerment and improving community welfare through the implementation of traditions. This research uses qualitative method. The data analyzed is field data using a historical and anthropological approach to religion. Data were obtained through observation, in-depth interviews, photovoice, documentation and library data. The results of this research show that Maudhu Lompoa tradition began to be implemented after Islam became the official religion of the Kingdom of Gowa in 1605. Maudhu lompoa (big birthday), namely the birthday of the Prophet Muhammad, was carried out as a method of spreading Islam where local elements became an important part of the tradition, such as traditional properties consisting of basic ingredients which are believed to have symbolic meaning as a hope for achieving prosperity. In its development, this tradition is carried out every year as proof of love for the Prophet Muhammad SAW and gratitude to Allah SWT. Maudhu Lompoa tradition has a series of activities where the integration of Islam is in the preparation and implementation stages. This tradition is not just a commemoration of birthdays but also a form of gratitude to Allah SWT and a symbol of society's hope to achieve prosperity. The Islamic cultural values and local culture that are integrated in this tradition include the spiritual dimension, social and community dimensions as well as the arts and entertainment dimension. The integration of Islam in this tradition has an impact on people's lives, including; increasing community religiosity and community welfare through economic empowerment.